Relations among Measures of Body Composition, Age, and Sex in the Common Marmoset Monkey (Callithrix jacchus) - Power, Rachel A.; Power, Michael L.; Layne, Donna G.; Jaquish, Cashell E.; Oftedal, Olav T.; Tardif, Suzette D. (Comparative medicine, 2001)
Few studies of body composition have been done in New World primates. In the study reported here, four methods of assessing body composition (body weight, anthropometry, labeled-water dilution, and total body electroconductivity) were compared in 20 marmosets, aged 0.96 to 7.97 years. Males and females did not differ in any measure (P > 0.05). Body weight ranged from 272 to 466 g, and body fat estimates varied from 1.6 to 19.5%. Strong positive correlations were observed between total body water and total body electroconductivity (R2 = 0.77), body weight and fat-free mass (males R2 = 0.95; females R2 = 0.91), and body weight and fat mass (males R2 = 0.86; females R2 = 0.85; P < 0.01). Male and female slopes were equivalent (P > 0.05) for the regressions of fat and fat-free mass against body weight. Positive correlations also were observed between girth measures and fat-free mass (R2 = 0.48 to 0.78) and fat mass (R2 = 0.60 to 0.74; P < 0.01). A good second- order polynomial relationship was observed between age and fat-free mass for the combined sample (R2 = 0.64). Results indicated that: subjects were lean; there was no sexual dimorphism relative to measures; body weight provided a reliable estimate of fat and fat-free mass; and within-subject body weight changes reflected a similar relationship between body weight and fat-free mass as did that across subjects.